Heterogeneity in psychiatric diagnostic classification. (September 2019) - Allsopp, Kate; Read, John; Corcoran, Rhiannon; Kinderman, Peter
Highlights: Theory and practice of diagnostic assessment is central yet contentious in psychiatry. DSM-5 contains heterogeneous diagnostic categories. Pragmatic criteria give clinical flexibility but undermine the diagnostic model. Trauma has a limited causal role in DSM-5, despite research evidence to the contrary. Abstract: The theory and practice of psychiatric diagnosis are central yet contentious. This paper examines the heterogeneous nature of categories within the DSM-5, how this heterogeneity is expressed across diagnostic criteria, and its consequences for clinicians, clients, and the diagnostic model. Selected chapters of the DSM-5 were thematically analysed: schizophrenia spectrum and other psychotic disorders; bipolar and related disorders; depressive disorders; anxiety disorders; and trauma- and stressor-related disorders. Themes identified heterogeneity in specific diagnostic criteria, including symptom comparators, duration of difficulties, indicators of severity, and perspective used to assess difficulties. Wider variations across diagnostic categories examined symptom overlap across categories, and the role of trauma. Pragmatic criteria and difficulties that recur across multiple diagnostic categories offer flexibility for the clinician, but undermine the model of discrete categories of disorder. This nevertheless has implications for the way cause is conceptualised, such as implying that trauma affects only a limited number of diagnoses despite increasing evidence to the contrary. Individual experiences and specific causal pathways within diagnostic categories may also be obscured. A pragmatic approach to psychiatric assessment, allowing for recognition of individual experience, may therefore be a more effective way of understanding distress than maintaining commitment to a disingenuous categorical system.